Biodegradation potential of phenol by pure and defined mixed cold-adapted bacterial consortia from Antarctica - Subramaniam, Kavilasni (2021)
The risk of phenol pollution from daily waste discharge and accidental oil spillage is ever-present due to increasing activities in the Antarctic continent, mainly related to the supply and operation of research stations and field expeditions, tourism, marine and air transportation. Increased levels of phenol concentration in the Antarctic environment bring significant risk to both aquatic and terrestrial biota due to its highly toxic properties and persistence. Sustainable human presence and activity in Antarctica require effective remediation technologies to be developed and their rapid application when required. The main purpose of the present study was to isolate new taxa of pure phenol-degrading bacteria from Antarctic soil and, both as a pure isolate and together with previously isolated phenol-degrading bacteria as a consortium, will be capable of rapid degradation of phenol at low temperatures (0-15°C). In addition, this study also focuses on identification of phenol-degrading pathway(s) of the pure culture, conventional and statistical optimisations of phenol degradation by both pure and mixed cultures, and the effect of heavy metals on phenol degradation by pure and mixed cultures. This thesis reports the isolation of a potential phenol-degrading bacterial strain (AQ5-15) from soil from King George Island, South Shetland Islands, Antarctica. This strain was identified as a member of the genus Arthrobacter based on 16S rRNA gene sequence analysis. Based on whole arest identified relative was suggested to be Paeniglutamicibacter sulfureus (99.38% similarity). Preliminary screening showed that strain AQ5-15 was capable of completely degrading 0.5 g/L phenol within 108 h at 10°C and it was selected for a detailed study. The genomic analysis identified the presence of genes encoding a complete pathway of aromatic compound metabolism in strain AQ5-15, consistent with the ability of the strain to utilise phenol as the sole carbon source. The genomic analysis was validated using enzyme assays of catechol 1,2-dioxygenase and catechol 2,3- dioxygenase, which confirmed the presence of the enzyme catechol 1,2- dioxygenase, consistent with the genes identified in the WGS. A study of the influence of parameters including nitrogen source, salinity, pH, and temperature was conducted to optimise the conditions for phenol degradation using onefactor- at-a-time (OFAT) and response surface methodology (RSM). Based on the results from OFAT, strain AQ5-15 showed the highest phenol degradation at 0.5 g/L (NH4)2SO4, 0.1 g/L NaCl, pH 7 and 20°C, proving that this strain is a psychrotolerant and prefers low salinity and near-neutral conditions. Statistical analysis of the results obtained from RSM showed that the strain could degrade phenol optimally at 0.5 g/L (NH4)2SO4, 0.13 g/L NaCl, pH 7.25 and 15°C, with pH and temperature identified as significant factors. This strain was mixed with two other previously isolated phenol-degrading strains (AQ5-06 and AQ5-07) in different combinations to further enhance degradation efficiency. The data obtained showed that mixture of strains AQ5-06 and AQ5-15 together could completely degrade 0.5 g/L phenol within 48 h at 10°C while mixture of strains AQ5-06, AQ5-07 and AQ5-15 together could completely degrade 0.5 g/L phenol within 60 h at 10°C. RSM analysis showed that the combination of strains AQ5- 06 and AQ5-15 could degrade phenol optimally at 0.4 g/L (NH4)2SO4, 0.13 g/L NaCl, pH 7.25 and 12.5°C, with only temperature as a significant factor. RSM analysis showed that the combination of strains AQ5-06, AQ5-07 and AQ5-15 can degrade phenol optimally at 0.4 g/L (NH4)2SO4, 0.13 g/L NaCl, pH 7.25 and 12.5°C, with ammonium sulphate concentration, sodium chloride concentration and temperature being significant factors. The tolerance levels of pure and mixed cultures towards different heavy metals that are widely present in Antarctic soils was studied by exposing strains AQ5-06, AQ5-07 and AQ5-15 individually as well as in consortia to the heavy metals Arsenic (As), Aluminum (Al), Copper (Cu), Zinc (Zn), Lead (Pb), Cobalt (Co), Cadmium (Cd), Chromium (Cr), Nickel (Ni), Silver (Ag) and Mercury (Hg) at an initial concentration of 1.0 ppm. Phenol degradation by strain AQ5-15 was inhibited when exposed to Cd, Ag and Hg while strain AQ5-06 was inhibited when exposed to Ag and Hg, and strain AQ5- 07 was inhibited when exposed to Cd and Hg. Consortia containing strains AQ5- 06 and AQ5-15 and all three strains were inhibited when exposed to Hg, Cd and Ag. In a nutshell, the attempt to develop highly efficient phenol-degrading bacterial consortia for significant inclusion in cold region bioremediation, specifically Antarctica was successful with a few limitations in the event of the co-occurrence of some heavy metals such as Hg, Cd, and Ag.